University Extension And Tourism: A Reflection On The Training Process For Tour Guides In Talamanca, Costa Rica. - Arias Hidalgo, David (2019)
This article presents key elements in the analysis of the university extension of the Instituto Tecnológico de Costa Rica (ITCR), in the particular case of the training experience of local indigenous guides and their constitution in the first indigenous tourism agency (AGITUBRIT) led by indigenous Bribris de Talamanca, in Costa Rica. The extension project was approached under a Participatory Action Research (PAR) approach. This experience is intended to reflect on the particularities of extension work such as the importance of participatory diagnosis, the periods of execution of an extension project, the suitability of the extension team, inter-institutional linkage, and the role of social sciences in university extension processes, mainly in an engineering-based university such as ITCR. The latter is concluded as a necessary element in the extension processes in order to promote a dialogue of knowledge between academia and native communities in the context of transdisciplinarity.